PEMBERIAN MANIPULASI MILLS PADA TERAPI ULTRASOUND (US) DAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAPAT LEBIH MENURUNKAN INTENSITAS NYERI PADA TENNIS ELBOW TIPE II - Ni Made Sulasih (Majalah Ilmiah Fisioterapi Indonesia, 2013)
Tennis elbow is a painful type II lateral epicondilus characterized by inflammation of the extensor carpi radialis brevis tendoperiosteal due to the use of the hand and wrist excessively, causing small tears in the extensor carpi radialis brevis tendoperiosteal. This study aimed to determine the additional Mill’s manipulation in the US and TENS therapy can further decrease pain in tennis elbow type II. The study was conducted with the design of pre-test and post-test control group, which found the number of samples for the control group with the intervention of the US and TENS as many as 14 people, and the treatment group by the US, TENS, and Mill’s manipulation as many as 14 people. From the results of hypothesis testing using two different test average is paired sample t-test in the control group obtained t value of 40.48 with a mean value of 49.93, p